2012
DOI: 10.1002/eji.201242478
|View full text |Cite
|
Sign up to set email alerts
|

CD34‐derived dendritic cells transfected ex vivo with HIVGag mRNA induce polyfunctional T‐cell responses in nonhuman primates

Abstract: The pivotal role of DCs in initiating the immune responses led to their use as vaccine vectors. However, the relationship between DC subsets involved in antigen presentation and the type of elicited immune responses underlined the need for the characterization of the DCs generated in vitro. The phenotypes of tissue-derived APCs from a cynomolgus macaque model for human vaccine development were compared with ex vivo-derived DCs. Monocyte/macrophages predominated in bone marrow (BM) and blood. Myeloid DCs (mDCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Cross‐linking of DCIR was shown to result in reduced IFN‐α induction upon TLR‐9 stimulation , and similar inhibitory effects were reported following incubation with the CLR ligand mannan . Interestingly, BDCA2 [our unpublished observation and documented at the NIH non‐human primate reagent resource portal (http://nhpreagents.bidmc.harvard.edu/NHP)] and DCIR were shown to be absent on pDC in rhesus macaques. Although not investigated here, a difference in the balance between activating TLRs and inhibitory CLRs could lead to different levels of pDC activation, possibly translating into a difference in cytokine production pattern.…”
Section: Discussionsupporting
confidence: 62%
“…Cross‐linking of DCIR was shown to result in reduced IFN‐α induction upon TLR‐9 stimulation , and similar inhibitory effects were reported following incubation with the CLR ligand mannan . Interestingly, BDCA2 [our unpublished observation and documented at the NIH non‐human primate reagent resource portal (http://nhpreagents.bidmc.harvard.edu/NHP)] and DCIR were shown to be absent on pDC in rhesus macaques. Although not investigated here, a difference in the balance between activating TLRs and inhibitory CLRs could lead to different levels of pDC activation, possibly translating into a difference in cytokine production pattern.…”
Section: Discussionsupporting
confidence: 62%
“…NHPs are a more relevant model than mice for the testing of human vaccines. We have previously demonstrated that NHP and human DC subsets have similar tissue distributions and bear analogous differentiation and activation markers, including C-type lectin receptors (9). Diverse DC populations can be identified in the macaque skin: LCs, which express langerin (CD207), are found exclusively in the epidermis while DC expressing DC-SIGN (CD209) are localized in the dermis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HQ738667.1). The 12E12 antibody binds efficiently to recombinant CD40 ectodomain from rhesus macaques and to DCs from cynomolgus macaques (15). A previous study showed that the dimeric HA1 domain expressed as a C-terminal H-chain antibody fusion can fully deplete protective anti-HA1 antibodies and can generate protective immune responses in mice (16).…”
Section: Animalsmentioning
confidence: 99%
“…KM246788). The 15C4 antibody binds efficiently to recombinant rhesus macaque LOX-1 ectodomain protein (S. M. Zurawski, unpublished data) and binds to CD11c ϩ and CD14 ϩ cells in the peripheral blood mononuclear cells (PBMCs) of cynomolgus macaques (12,15). Anti-human DCIR 9E8-NP (GenBank accession no.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation